Recipient and instructor perspectives of an adapted exercise-based fall prevention programme for adults aged 50+ years with vision impairment: a qualitative study nested within a randomised controlled trial - Lisa Keay; Lindy Clemson; Helen Nguyen; Lisa Dillon; Kirsten Bonrud Jakobsen; Jodi Martin; Frances Tinsley (BMJ Open)
Objective Older adults with vision impairment currently have no access to tailored fall prevention programmes. Therefore, the purpose of this study, nested within an ongoing randomised controlled trial (RCT), is to document the adaptation of an existing fall prevention programme and investigate the perspectives of instructors involved in delivery and the older adults with vision impairment receiving the programme (recipients).Design We documented programme adaptations and training requirements, and conducted semistructured, individual interviews with both the instructors and the recipients of the programme from 2017 to 2019. The content of each interview was analysed using behaviour change theory through deductive qualitative analysis.Setting New South Wales and Australian Capital Territory, Australia.Participants The 11 trained instructors interviewed were employees of a vision rehabilitation organisation and had delivered at least one programme session as part of the RCT. The 154 recipients interviewed were community-dwelling adults aged ≥50 years with vision impairment and no diagnosis of dementia, and had completed their participation in the programme as part of the intervention group of the RCT.Results Six key themes were identified relating to recipient (delivery aptitude, social norms, habit formation) and instructor (individualised adaptation, complimentary to scope of practice, challenges to delivery) perspectives. With initial training, instructors required minimal ongoing support to deliver the programme and made dynamic adaptations to suit the individual circumstances of each recipient, but cited challenges delivering the number of programme activities required. Recipient perspectives varied; however, most appreciated the delivery of the programme by instructors who understood the impact of vision impairment.Conclusions and implications This novel qualitative study demonstrates that the adapted programme, delivered by instructors, who already have expertise delivering individualised programmes to older people with vision impairment, may fill the gap for a fall prevention programme in this population.Trial registration number ACTRN12616001186448.